In-Service Training Needs of Hotel Receptionists in Enugu State, Nigeria - Chinwe Asogwa; Paulina Offiong; Ifeanyi Jude Osuoha (International Journal of Home Economics, Hospitality and Allied Research, 2025)
The study focused on determining the in-service training needs of receptionists for improved service delivery of hotels in Enugu State, Nigeria. Three research questions were used and one null hypothesis was tested. Descriptive survey design was adopted in carrying out the study. The population of the study comprised of 847 which consist of 298 managers of registered hotels and 549 hotel receptionists from Enugu state. A purposive sampling technique was used to select 116 hotels in Enugu urban. The instrument for data collection was structured questionnaire. The instrument was face validated by three experts while the reliability of the instruments was determined using Cronbach’s Alpha method. Copies of the questionnaire were distributed by the researcher with the help of four research assistants. Mean will be used to answer all the research questions, standard deviation will be used to determine the degree of deviation from the mean while ANOVA was used to test the null hypotheses at 0.05 level of significance. The results of the findings revealed that guests are given wristbands that contain information to obtain entry to their rooms. The receptionists highly needed seven items while one item was averagely needed as conflict management skills needed by receptionists for improved service delivery of hotels in Enugu state and there was no significance difference among the mean responses of hotel managers, receptionists and guests on the technology proficiency skills, conflict management skills and multi-tasking & prioritizing skills needed by the receptionists to improve service delivery of hotels in Enugu State. Based on the findings, it was therefore recommended that hotel managers should organize in-service training for their receptionists to improve their service delivery thereby maximizing hotel profits